P.166 Assessment of External Ventricular Catheter Associated Infections at the Ottawa Hospital: Literature Review and Quality Improvement Initiative. (November 2021) - Ben Nakhi, S; Drake, B; English, S
Abstract : Background: External ventricular drains are a lifesaving intervention in the management of acute hydrocephalus. EVD associated infections vary significantly, and expert panels recommend reviewing institutional policies if infection rates exceed 10%. The audit aims to identify the infection rate at our institution, whereas the literature review aims to synthesize a new institutional EVD best practice guideline. Methods: An audit of EVD catheters inserted in the time period between 07/01/2019 and 10/25/2020 was conducted. Statistical analysis to calculate absolute incidence, infections per 1000 days of catheter use. A literature review to identify best practices for the insertion and management of EVDs was conducted. Results: 75 patients required a total of 105 EVD catheters. There were 16 (15.3%) EVD related infections, equating to 14.3 infections per 1000 days. Fifty percent of patients developed an EVD related infection within 9 days of insertion. Most infections were induced by skin flora (87.5%). A comprehensive step-by-step EVD insertion and management protocol was developed aiming to reduce the risk of infection. Conclusions: The incidence of EVD associated infections at the Ottawa Hospital is significantly higher than acceptable rates as suggested by expert panels. A new evidence-based best practice guidelines should be implemented. A follow-up audit is necessary.